Metformin use is associated with a reduced risk of cognitive impairment in adults with diabetes mellitus: A systematic review and meta-analysis - Zhang, Jia-Hao; Zhang, Xin-Yang; Sun, Yan-Qiu; Lv, Ren-Hua; Chen, Mei; Li, Meng (Frontiers in Neuroscience, 2022)
Objective Controversy exists regarding the impact of metformin and whether it prevents or promotes the incidence of cognitive dysfunction. This systematic review and meta-analysis were conducted to identify the effect of metformin therapy on cognitive function in patients with diabetes. Methods Electronic databases (PubMed, EMBASE, PsycINFO, the Cochrane Library, and Web of Science) were systematically searched by two investigators from the date of inception until March 1, 2022. The study followed PRISMA guidelines. Inclusion criteria were defined according to the PECOSmodel. Eligible studies investigated cognitive dysfunction in metformin users compared with non-users in adults with diabetes. Only observational study designs (such as cohort, cross-section, and case-control) were included. Results A systematic search identified 1,839 articles, of which 28 (17 cohort, 8 case-control, and 3 cross-sectional studies) were included in the meta-analysis. Metformin reduced the occurrence of cognitive impairment in patients with diabetes [unadjusted hazard ratio (HR) = 0.67, 95% CI: 0.62–0.73; adjusted hazard ratio (aHR) = 0.92, 95% CI: 0.85–0.99]. In addition, the use of metformin was associated with a decreased risk of dementia (HR = 0.64, 95% CI: 0.59–0.69; aHR = 0.90, 95% CI: 0.84–0.96), while a random-effects meta-analysis indicated no significant effect of metformin on the risk of Alzheimer's disease (AD) (HR = 0.85, 95% CI: 0.60–1.22; aHR = 1.10, 95% CI: 0.95–1.28). Conclusion Metformin therapy decreased the occurrence risk of cognitive decline in patients with diabetes mellitus. Moreover, the use of metformin by adults with diabetes for the prevention of dementia, but not AD, is supported by the available evidence.